Finite Element Analysis of Natural Thawing Heat Transfer of Artificial Frozen Soil in Shield-Driven Tunnelling - Yong Fu; Jun Hu; Jia Liu; Shengbin Hu; Yunhui Yuan; Hui Zeng (Advances in Civil Engineering)
The technology of artificial horizontal freezing method is increasingly being used in the soil reinforcement of urban underground projects such as shield-driven tunnelling. Compared with the freezing process, the thawing process is more complicated, and the thawing behavior of artificial frozen soil surrounding shield-driven tunnels has not been well investigated in both the academic and industrial domains. This study, therefore, aims to investigate the natural thawing heat transfer behavior of artificial horizontal frozen soil in shield-driven tunnelling using a three-dimensional finite element method. The finite element modelling is based on the horizontal freezing reinforcement project of Chating Station to Jiqingmen Station Tunnel in the Nanjing Metro Line 2. Validation between finite element results and site measured results is firstly conducted. The natural thawing temperature field contours as well as the radial and longitudinal distributions of natural thawing temperature in the frozen soil surrounding the tunnel are then explicitly examined. Furthermore, sensitivity analysis of influencing factors such as the thermal conductivity, latent heat of phase change, ambient temperature inside tunnel, freezing time, and original ground temperature is carried out. The results and findings of this study may enrich the current limited database and enable a better understanding of natural thawing heat transfer behavior of artificial frozen soil in shield-driven tunnelling.